Effects of vitamin D addition for laying hens in the final third of production on egg quality (Research, Society and Development, 2022)
This study determined whether supplementing the diet of laying hens in the final third of laying with vitamin D improves bird health and egg performance and quality. The hens were separated into four groups with six repetitions each and five animals per repetition to test three doses of vitamin D supplementation (50, 100, and 150 mg/kg). The vitamin D supplementation had no effect on the hens performance; however, when we individually evaluated each repetition, we found that the birds of T100 and T150 showed significant increases (P